2020
DOI: 10.1177/0047239520953792
|View full text |Cite
|
Sign up to set email alerts
|

The Development of 21st-Century e-Learning Module Assessment Tool

Abstract: The emergence of 21st-century skills convinced educational institutions in modifying teaching styles, which lead to the introduction of blended, flipped, and personalized learning. Studies demonstrated present-day best practices, but none provided a practical assessment procedure. Thus, this study aimed to develop a tool in evaluating learning modules—the 21st-century e-Learning Module Assessment Tool. Identification of components for the instrument revealed the interrelating nature of blended, flipped, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In the context of online learning, CoI presents three critical elements of a meaningful learning experience: (1) social presence, (2) teaching presence, and (3) cognitive presence (Krzyszkowska & Mavrommati, 2020). Although focused on blended instead of purely online learning, the twenty-first Century e-Learning Assessment Tool (21CELMAT) provides nine components of learning modules: (1) selfpaced learning, (2) out-of-class activities, (3) live events, (4) in-class activities, (5) collaborative activities, (6) diagnostic assessments, (7) summative assessments, (8) flexibility, and (9) personalization (Calamlam, 2021). Despite their overlapping components, each online learning framework has established its own distinct themes.…”
Section: Online Distance Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of online learning, CoI presents three critical elements of a meaningful learning experience: (1) social presence, (2) teaching presence, and (3) cognitive presence (Krzyszkowska & Mavrommati, 2020). Although focused on blended instead of purely online learning, the twenty-first Century e-Learning Assessment Tool (21CELMAT) provides nine components of learning modules: (1) selfpaced learning, (2) out-of-class activities, (3) live events, (4) in-class activities, (5) collaborative activities, (6) diagnostic assessments, (7) summative assessments, (8) flexibility, and (9) personalization (Calamlam, 2021). Despite their overlapping components, each online learning framework has established its own distinct themes.…”
Section: Online Distance Learningmentioning
confidence: 99%
“…The purpose of this analysis was to statistically test the significance of differences in post-test scores between students with higher and lower SRL scores. Post-test scores were entered as the dependent variable, SRL score (higher and lower groups), and academic year (AY 2020-2021and AY 2021-2022 as independent variables. Pre-test scores were entered as a covariate.…”
Section: Effect Of Digital Note-taking On Business Math Achievementmentioning
confidence: 99%
“…There is also a concept of blended learning, which involves the combination of traditional classroom learning with e-learning strategies. Research has shown that this method is more effective and provides more opportunities for the productive interaction between students and teachers (Calamlam, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is obvious that new learning methods need to be introduced into the curriculum; these should involve not only the improvement of traditional pedagogical practices but also the introduction of online and mobile learning technologies into the curriculum (interactive tasks, educational mobile applications and games, online lessons, etc.) (Calamlam, 2021;Hodges & Weber, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Rodriguez and Armellini (2013), there are three types of interactions that are crucial in making an online classroom a learning environment: learner–content interaction where learners engage with the learning content and tools provided in online classrooms; learner–learner interaction where learners are given opportunities to work and share ideas with their peers; and learner–teacher interaction where learners communicate with instructors who are regarded as experts in the subject they teach. In a completely online environment, instruction could be delivered through self-paced activities or live event sessions (Calamlam, 2020). Self-paced activities, commonly known as asynchronous instruction, refer to instructions that learners experience individually.…”
Section: Introductionmentioning
confidence: 99%